Pengaruh Daya Repelensi Tanaman Zodia, Rosemary dan Sereh Wangi terhadap Nyamuk Aedes Aegypti - Itsna Hidayati; Iswanto Iswanto; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Dengue Haemorrhagic Fever (DHF) is an environmental based disease that transmitted by Aedes aegypti mosquitoes. There are three efforts to control Aedes aegypti, one of which is the useof anti mosquito plants that is categorized as biological control. This study was aimed to determine the effect of repelling power of three anti-mosquito plants (Zodia, Rosemary and Citronella)in the form of intact and chopped exposure on Aedes aegypti. The study was an experiment withpost test only design. The observation shows that the highest number of Aedes aegypti mosquetoes was repelled by chopped Zodia, i.e. 36 % or 17,99 mosquitoes in average; and the lowestnumber is by Citronella in the form of whole plant, i.e.7 % or 3,63 mosquitoes in average. Oneway Anova test obtained a p-value of <0,001; which means that the difference of the number ofmosquito repelled by each treatments is significant, and can be interpreted that the repelling power among the all treatments is significantly different. To conclude, the best repellent is choppedZodia.